The Effect Of Crude Extract Green Mussel (Perna viridis) With Intramuscular Injection In Promoting Pangas Catfish (Pangasius hypothalamus) Gonadal Maturation - Noor, Nuning Mahmudah; Indariyanti, Nur; Marya, Dina Tri; Kurniawan, Agung (ABEC Indonesia, 2024)
The management of broodstock is a crucial step in the fish breeding process. The size of the body andgonadal maturity are significant aspects of broodstock quality in aquaculture. To produce high-quality fish, thebrood needs to possess fully grown gonads and an ideal body size. According to several studies, green musselextract is thought to stimulate zebrafish growth and gonad maturation caused by estradiol compounds, althoughfurther testing on other fish, such as the Pangasius hypothalamus, has not yet been done. This research aims toevaluate the effect of administering crude green mussel extract containing estradiol compound via intramuscularinjection on the growth and maturation of pangas catfish gonads. The pangas catfish broodstock was treated with aninjection of green mussel extract and ovaprim at a dose of 0.5 mg/broodstock with three repetitions over a 30-daymaintenance period. The results show that the administration of green mussel extract at a dose of 0.5 mL/kgincreases weight growth. The homogeneity level of eggs in female pangas catfish induced with green musselextract is the same diameter as induction with ovaprim and slightly different from the control specimen (withouttreatment). The results show that the crude extract of green mussels in the methanol fraction, at a dose of 0.5mL/kg, can increase growth and egg diameter.